(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
We have measured the reflectivity of Bi12Ti0.8Ga0.2O20 single crystal at room temperature using energy range from 1.5 to 6eV. Top Seeded Solution Growth (TSSG) technique has been used to produce mixed Bi12Ti0.8Me0.2O20 single crystals in which Ti was substituted with gallium Ga ions. The results are qualitatively interpreted in terms of the presence of gallium. These structures have been assigned to transitions from energy bands derived mainly from the O2p states and the Bi-O bonding states. As a result, two main effects associated with Ga states have been observed in the spectra. The first is a significant energy shifting of the critical points with respect to Bi12TiO20 single crystal. The second is a broadening of the characteristic reflectivity maxima. These results reveal a stronger interaction between O2p and Ga4p states close to the top of the valence band maximum (VBM). تم قياس الانعكاسية للبلورة الأحادية Bi12Ti0.8Ga0.2O20 عند درجة حرارة الغرفة باستخدام مجال الطاقة من 1.5 إلى eV 6. استخدمت تقنية التنمية العلوية من خلال بذرة المحلول (Top Seeded Solution Growth) (TSSG) لإنتاج بلورات أحادية مختلطة من النوعBi12Ti0.8Me0.2O20 ، حيث حلت أيونات الغاليوم Ga محل أيونات التيتانيوم Ti. فسرت النتائج نوعياً بوجود ذرات الغاليوم. أسندت البنى الطيفية الملاحظة في القياس إلى الانتقالات من عصابات الطاقة الناتجة من السويات O2p بشكل رئيسي وسويات الارتباط Bi-O. نتيجة لذلك، لوحظ في أطياف القياس أثرين رئيسين مرتبطين مع سويات الغاليوم. الأول هو انزياح كبير لطاقة النقاط الحرجة نسبة إلى البلورة الأحادية Bi12TiO20. والثاني هو تعرض نطاق قمم الانعكاسية المميزة . تكشف هذه النتائج عن تفاعل قوي بين السويات O2p والسويات Ga4p بقرب أعلى عصابة التكافؤ (VBM).